Creating meaning: Developing students understanding of Indigenous community issues in prose class - Sri Sumaryani; Imas Istiani; Lutfi Ashar Mauludin; Almira Irwaniyanti Utami (Universitas Syiah Kuala, 2024)
This study investigated the significance of discussing a literary work written by an Indigenous American author to students general understanding of the socio-cultural, economic, and political issues of the Indigenous communities (ICs) in Indonesia. A total of 153 students who enrolled in the Prose Class at the English Literature Study Program at Universitas Negeri Semarang participated in the study. This study adopted a pedagogical application model consisting of pre-reading activities, general comprehension, and connecting literary text with social context. The treatment was part of an attempt to incorporate local ICs content in the learning process and make it mainstream. This research employed a mixed method, and the participants completed the pre and post-tests as the quantitative data. In addition, an open-ended questionnaire and observation were used to collect the qualitative data. We employed Freires critical pedagogy to descriptively analyze the treatment process and results. The findings revealed that the treatment improved the students understanding of the issues faced by the ICs in Indonesia. They could comment critically on the issues during the discussion activity and fill in the knowledge gaps in the pre-test result. This study also suggested the integration and discussion of the ICs local values and issues into the education materials and texts to develop students critical thinking skills.